Procedure to develop binodal curve and phase diagram for aqueous two-phase system - Mohd Arshad, Zatul Iffah; Amid, Azura (Springer Nature, 2018)
Purification of protein is normally involved an expensive downstream processing step. For large scale manufacturing facilities, identification of an economical procedure is the most advantage. Aqueous Two-Phase System (ATPS) is a technique that suitable to be used in extracting protein from the mix culture supernatant. The process is also economical. However, there are a few tricky parts that the researchers need to master before this technique can be applied. Therefore, this chapter presents the step by step procedure in optimizing this technique.